ANALYSIS OF HOUSING LOAN PROCEDURES TO SUPPORT INTERNAL CONTROL (Case Study At PT. Bank Tabungan Negara Sub-branch Sawojajar malang) - Rusyda Aisyati Amrullah (Jurnal Administrasi Bisnis, 2013)
As a developing country, Indonesia's economy is affected by the fluency of banking stream. The role of banks is significant to assist the venture capital provision in the form of credit. Business in Indonesia, both small and large enterprises are still depending their capital source from bank lending. In this case credit has become an important activity for every bank. Because, usually banks obtain bigger income from credit than other bank services. The interest becomes banks source of income, provision, and bank's administrational costs. The research objective is toodescribe the implementation of housing loans allocation procedures, to describe how the procedures of housing loans allocation can support internal control. Based research finding implementation for procedures of housing loans allocation until loans disbursement is good enough where bank has used the principle of 5C. The weakness of this bank is still there overlapping performed by the department. Key word : Analysis Procedures of Housing Loan Allocation